(untitled) (Research, Society and Development, 2022)
The use of dual-purpose wheat emerges as an agricultural strategy to maximize soil use, mainly for forage and grain production, aiming to enhance natural resources in the autumn and winter seasons in Rio Grande do Sul. The objective of this work was to evaluate the effect of nitrogen rates on the production of pre-dried and wheat grains cv. BRS Pastoreio. The study consisted of eight treatments resulting from the factorial arrangement of four nitrogen (N) doses x two managements allocated in a randomized block design. The N rates were 70, 100, 130 and 160 kg/ha and the management consisted of: (1) only grain yield and (2) forage harvest for pre-dried silage and sprouting for grain production. The grain yield of the sprouting of plants harvested as pre-dried was drastically reduced. Nitrogen fertilization did not affect the yield components of dual-purpose wheat in the two managements studied. There was an effect of nitrogen doses on forage production in management 2. Regardless of the nitrogen dose, the CP content of pre-dried sprouting grains was higher than the exclusive management for grains.